Developing Students’ Vocabulary Mastery Through Mind-Mapping Techniques for Seventh Grades at SMP Negeri 32 Semarang - Salwa Farikha Aswa; Senowarsito; Sri Wahyuni (Indo Publishing, 2025)
This study aims to examine the potential of mind mapping methods to enhance seventh-grade students' vocabulary mastery at SMP Negeri 32 Semarang. This research was motivated by students’ difficulties in remembering new vocabulary due to monotonous and teacher-centered methods. By using mind mapping in a visual format, students were encouraged to arrange vocabulary systematically and build stronger word relationships in descriptive writing. A quasi-experimental method was used, involving class VII G as the experimental class and VII B as the control class. Data were collected using both pre- and post-tests in multiple-choice format. The results were analyzed using tests for normalcy and homogeneity, validity and reliability, and a t-test with SPSS 21. The findings show that the experimental class improved from a mean score of 69.67 to 81.67, while the control class improved from 63.00 to 79.67. The t-test result Sig. 0.000 < 0.05 confirmed a significant difference between both of the groups. The results imply that applying mind mapping yields better outcomes than traditional strategies in developing students’ vocabulary skills.